2013
DOI: 10.1186/2191-0855-3-44
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial action and anti-corrosion effect against sulfate reducing bacteria by lemongrass (Cymbopogon citratus) essential oil and its major component, the citral

Abstract: The anti-corrosion effect and the antimicrobial activity of lemongrass essential oil (LEO) against the planktonic and sessile growth of a sulfate reducing bacterium (SRB) were evaluated. Minimum inhibitory concentration (MIC) of LEO and its major component, the citral, was 0.17 mg ml-1. In addition, both LEO and citral showed an immediate killing effect against SRB in liquid medium, suggesting that citral is responsible for the antimicrobial activity of LEO against SRB. Transmission electron microscopy reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 36 publications
3
32
0
2
Order By: Relevance
“…The hydrocarbons and sulfate in crude petroleum may serve as electron donors and terminal electron acceptor for SRB, respectively . Thus, SRB can grow in crude petroleum.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrocarbons and sulfate in crude petroleum may serve as electron donors and terminal electron acceptor for SRB, respectively . Thus, SRB can grow in crude petroleum.…”
Section: Resultsmentioning
confidence: 99%
“…LG oil showed aggregation and deformities [45]. Korenblum et al also stated that both LG oil and its major component, citral showed an immediate killing effect against sulfate reducing bacteria, suggesting that citral was responsible for the antibacterial activity of LG oil [46]. The SEM micrographs explains that the LGME-AZM formulation in comparison with the pure drug AZM has an enhanced antibacterial property against pathogenic bacterial strains.…”
Section: Determination Of Cell Viabilitymentioning
confidence: 99%
“…Essential oils are incorporated into these films because they contain phenolic compounds with antibacterial and antifungal activities (Korenblum et al ., ; Jo et al ., ). Among essential oils, lemongrass ( Cymbopogon citratus ) oil (LE) has been incorporated into the edible films such as gelatin and alginate‐apple puree film to provide the antimicrobial activity (Rojas‐Grau et al ., ; Ahmad et al ., ; Tongnuanchan et al ., ).…”
Section: Introductionmentioning
confidence: 98%